TT genotype of the methylenetetrahydrofolate reductase C677T polymorphism is an important determinant for homocysteine levels in multi-ethnic Malaysian ischaemic stroke patients - Mejia Mohamed, E.H.; Tan, K.S.; Ali, J.M.; Mohamed, Z. (2011)
Introduction: The functional point mutation C677T in the methylenetetrahydrofolate reductase (MTHFR) gene, has been reported to contribute to hyperhomocysteinaemia which is a risk factor for atherothrombotic ischaemic strokes. This study evaluated the prevalence of the C677T polymorphism of the gene in Malaysian ischaemic stroke subjects of Malay, Chinese and Indian ethnicities, and its association with homocysteine levels (tHcy). Materials and Methods: A total of 292 subjects were recruited, comprising 150 ischaemic stroke patients and 142 control subjects who were age and sex matched. Plasma homocysteine, serum folate and vitamin B12 were measured in all subjects. Genotyping was carried out using PCR-RFLP. Results: The homocysteine levels were signifi cantly higher (P = 0.001) in the stroke group (11.35 Â± 2.75 Î¼mol/L) compared to the control group (10.38 Â± 2.79 Î¼mol/L). The MTHFR C677T genotype distribution for the stroke group was 46, 40 and 14, respectively for CC, CT and TT genotypes and 59.9, 33.8 and 6.3, respectively for the control group. The genotype and allelic frequencies were signifi cantly different between the 2 groups, with P = 0.02 and P = 0.004 respectively. No signifi cant difference was seen in the genotype distribution inter-ethnically. An increasing tHcy was seen with every additional T allele, and the differences in the tHcy for the different genotypes were signifi cant in both the control (P <0.001) and stroke groups (P <0.001). Conclusion: This study shows that TT genotype of the methylenetetrahydrofolate reductase C677T polymorphic gene is an important determinant for homocysteine levels in Malaysian ischaemic stroke patients.